The Cyber Proxy War: Non-State Actors Role in Global Geopolitical Competition - Hafizd Alharomain Lubis; Mohammad Izdiyan Muttaqin; Nurwahidin Nurwahidin (Publikasi Indonesia, 2025)
Cyberwarfare has become one of the most prominent aspects of global geopolitical competition, introducing a new dimension of conflict involving states and non-state actors. Although research on the role of states in cyber warfare has been amplacious, research on the role of non-state actors is still limited. This study aims to analyze the role and impact of non-state actors in global cyber warfare. In cyber warfare, non-state actors can exploit the vulnerabilities of security systems to achieve their political or ideological goals, changing geopolitical dynamics in unexpected ways. Case studies raised in this study include cyber attacks by Anonymous groups against governments and companies, cyber acts of terrorism by ISIS, manipulation of information by extremist groups to achieve their political goals, and the use of digital propaganda in regional conflicts. By paying attention to the concept of force and security in the perspective of realism, this research is expected to provide a better understanding of how non-state actors influence global geopolitical dynamics through cyber warfare. The implication of this research is the importance of strengthening national cyber defense and international cooperation in the face of threats presented by non-state actors in the cyber domain.